2020
DOI: 10.1101/2020.11.04.367730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CaveThiovulaceaediffer metabolically and genomically from marine species

Abstract: Life in Movile Cave (Romania) relies entirely on primary carbon fixation by bacteria oxidizing sulfide, methane and ammonia with oxygen, nitrate, sulfate, and ferric iron. There, large spherical-ovoid bacteria (12-16 µm diameter), rich in intracellular sulfur globules, dominate the stable microbial community in the surface water of a hypoxic Air Bell. These were identified as Thiovulum sp. (Campylobacterota). We obtained a closed genome of this Thiovulum and compared it to that of Thiovulum ES. The genes for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 117 publications
(201 reference statements)
0
5
0
Order By: Relevance
“…Similar metabolic traits were found for the recently characterized Thiovulum sp. that dominates Movile Cave's hypoxic Air Bells microbial mat [22]. Moreover, Arcobacteraceae family was found dominant in the white filaments from the thermal sulfidic spring of Fetida Cave, Italy [56].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar metabolic traits were found for the recently characterized Thiovulum sp. that dominates Movile Cave's hypoxic Air Bells microbial mat [22]. Moreover, Arcobacteraceae family was found dominant in the white filaments from the thermal sulfidic spring of Fetida Cave, Italy [56].…”
Section: Discussionmentioning
confidence: 97%
“…Here, an active redox interface is created on both the water's surface and cave walls, colonized by floating microbial mats and biofilms. Most of our knowledge of this ecosystem comes from studies of trophic chain components such as microbial mats associated with the surface of the hydrothermal water and its close proximity [19][20][21][22]. In addition, the rich endemic invertebrates of Movile Cave live in the proximity of the sulfidic water.…”
Section: Introductionmentioning
confidence: 99%
“…Similar metabolic traits were found for the recently characterized Thiovulum sp. isolated from Movile Cave’s hypoxic Air Bells microbial mat [22]. Moreover, Arcobacteraceae family was found dominant in the white filaments from the thermal sulfidic spring of Fetida Cave, Italy [56].…”
Section: Discussionmentioning
confidence: 99%
“…Here, an active redox interface is created on both the water's surface and the walls of the cave, which are colonized by floating microbial mats and biofilms. Most of our understanding of this ecosystem comes from studies on trophic chain components such as microbial mats associated with the hydrothermal water surface and its close proximity [19][20][21][22]. In addition, the rich endemic invertebrate fauna of Movile Cave gravitates in the proximity of the sulfidic water, being most abundant in the Air-Bells and Lake Room [15,19] where the redox potential is higher, particularly in the Air-Bells water surface [23].…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacterota was also found to be a dominant group in the only microbiological survey on whale fall performed in the south Atlantic Ocean to date (Cavalett et al 2017). The authors reported that sediment samples collected underneath a whale carcass found at 4200 m contained high proportions of Epsilonproteobacteria - the taxa previously assigned to this class are now included in the phylum Campylobacterota, according Silva v. 138 (Bizic et al 2020). We also detected Gammaproteobacteria S-oxidisers, mainly from the family Thiomicrospiraceae.…”
Section: Discussionmentioning
confidence: 99%